PediaStat ambulatory, urgent, and emergency pediatrics - Orenstein, Julian; Klein, Bruce L.; Mayer, Thom A.; Medifor (Firm) (Port Townsend, WA : Medifor, 1999)
(Producer) Reference tool containing 285 chapters written by 174 authors. Contains over 500 color illustrations and images. Each chapter includes a brief overview of the disease, patient assessment, and acute care management criteria from pre-hospital to disposition. Includes Lexi-Comp's Pediatric dosage handbook for links to drug therapies
CD is available at Koleksi Media, Perpustakaan HUKM
System requirements: 486 processor (Pentium recommended); 8MB RAM (16 recommended); Windows 95/98 & NT; graphics card; monitor with 16 bit color graphics capability or higher; CD-ROM drive
System requirements: Macintosh, PowerPC; 16MB RAM; System 7.5 or higher; monitor with thousands of colors capability; CD-ROM drive
Keywords: Emergencies -- child; Emergency Medical Services; Pediatrics